Pengembangan Eksperimen Virtual Model Science, Environtment, Technology and Society berbasis Augmented Reality Materi Ekosistem untuk Meningkatkan Keterampilan Pemecahan Masalah dan Sikap Peduli Lingkungan - Prisca Arzita Perdana*; Dadan Rosana (Jurnal Pendidikan Sains Indonesia, 2023)
The era of globalization demands human resources who have the ability to solve problems. The observation results found that students lack problem solving skills and the formation of an attitude of caring for the environment. This study aims to produce a virtual experimental learning model for ecosystem material based on augmented reality to improve students' problem-solving and environmental care attitudes that are feasible, practical and effective. This research is development  using the 4D model developed by S. Thiagarajan which consists of 4 stages, namely definition, planning, development and deployment. This research was conducted at SMP N 1 Salam. The research design used a pretest-posttest control group design. The results showed that: 1) virtual experiments on the SETS learning model for ecosystem material based on augmented reality was assessed for its feasibility by material experts in the very good category, media experts in the good category, and science teachers in the good category; 2) can improve problem solving skills as indicated by the highest n-gain score, namely experimental class VII E, namely 0.7. The results of the calculation of the Manova test, a significant value of 0.00 was obtained. These results indicate that in the final condition after treatment there is a significant difference in the average problem solving and environmental care attitude between the experimental class and the control class. It can be concluded that virtual experiment of the SETS learning model for AR-based ecosystem material is used by teachers to improve problem solving skills and students' environmental care attitudes